Ekonomi Politik Media Pada Strategi Televisi Lokal BRTV Dalam Mempertahankan Eksistensi - Amelia, Dita Via; Yusup, Eka; Widya Budhiharti, Tri (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research discusses BRTV's local television strategy in maintaining its existence in the midst of broadcasting industry competition after making the switch from analog to digital signals. Using Vincent Mosco's theory of media political economy, this research aims to understand how BRTV faces challenges and capitalizes on opportunities in a changing media environment. A qualitative research method with a descriptive approach was used, involving interviews, observation, and documentation to obtain data from the company. The results show that BRTV implements various strategies, including the utilization of programs and social media, attracting advertisers by targeting specific audience ages, and recruiting with specific criteria. Challenges faced include audience shift to online platforms, competition with online media, and employee attrition during the pandemic. BRTV's strengths include awards received from KPID West Java. To overcome obstacles and challenges, BRTV focuses on program innovation, content creativity, and recruitment for new positions. This research provides insight into BRTV's efforts in dealing with the dynamics of the local broadcasting industry